Field Trip Kereta Cepat Whoosh untuk Mengembangkan Kecerdasan Kinestetik Siswa TK Laboratorium UPI CIbiru - Faisal Muzzamil; Sulastri; Arkais Agapita (Yayasan Al-Afif, 2026)
Field trip is an implementation of learning based on experiential learning as developed by David Kolb. At UPI Cibiru Bandung Laboratory Kindergarten, this field trip activity is one of the flagship programs and routine activities carried out every academic year. In the 2025 academic year, UPI Cibiru Laboratory Kindergarten carried out a field trip activity in the form of learning about the Whoosh High-Speed ​​Train. Based on the background of the UPI Cibiru Laboratory Kindergarten Whoosh High-Speed ​​Train field trip activity, the purpose of this research is to reveal more deeply and describe more clearly the following points, namely: (1) Realization of the UPI Cibiru Laboratory Kindergarten Whoosh High-Speed ​​Train Field Trip Activity; (2) Developing the Kinesthetic Intelligence of UPI Cibiru Laboratory Kindergarten Students Through the Whoosh High-Speed ​​Train Field Trip Activity. This research uses the Case Study method. This research is based on the Embodied Cognition theory initiated and developed by Varela, Thompson & Rosch. Based on the results of empirical observations, two strategic findings were obtained in this research, namely: (1) The Whoosh High-Speed ​​Train field trip activity was realized through four activity agendas consisting of introduction to the Whoosh High-Speed ​​Train Station environment, practice of ordering Whoosh High-Speed ​​Train tickets, traveling on the Whoosh High-Speed ​​Train, and learning on the Whoosh High-Speed ​​Train; (2) the development of kinesthetic intelligence through the Whoosh High-Speed ​​Train field trip activity was carried out in four ways consisting of direct experience learning at the Whoosh High-Speed ​​Train Station, direct practice of how to order Whoosh High-Speed ​​Train tickets, experiencing the journey directly using the Whoosh High-Speed ​​Train, and direct learning by the Whoosh High-Speed ​​Train Flight Attendant.